Liquidity score and bid-ask spread nexus: Empirical researchon exchange traded bonds - Ercegovac, Roberto; Pivac, Snježana; Vuković, Marija (Oeconomica Jadertina, 2024)
Recognition of the liquidity of financial assets is importance management and accounting requirement in holding of the bank or trade book of financial security position. Financial theory explains the securities prices bid-ask spread and market liquidity nexus. Market liquidity decreases inventory costs of market makers and reduces the spread value. After the 2007 global financial crisis, Bloomberg has developed a new comprehensive measure of liquidity, accepted by market professionals. Finding the liquidity score and bid-ask spread nexus is the base research objective of the paper. The research of the correlation between bid-ask spread and liquidity score value is done on the public listed fixed income securities on Euronext and London Stock Exchange. The significant negative relations exist only on high liquid debt securities, as well as non liquid securities. Researching results can be used in investing decisions strategies and in security portfolio classification under the International Financial Reporting Standards requirement.
Keywords: liquidity measures, bid-ask spread, liquidity score, IFRS 13